Reproductive isolation between sister species of Iberian pine voles, Microtus duodecimcostatus and M. lusitanicus. Issue 2 (4th March 2019) - Cerveira, Ana M.; Soares, Joana A.; Bastos-Silveira, Cristiane; Mathias, Maria da Luz
Abstract : Contact zones of recently diverged species provide the ideal opportunity to study the nature of reproductive barriers. The Mediterranean ( Microtus duodecimcostatus ) and Lusitanian pine voles ( M. lusitanicus ) are a pair of recently diverged sister species endemic to Western Europe. Recent microsatellite data raised the possibility that hybridisation events, although rare, may still occur in the area of sympatry of both species. Here we evaluated the nature and extent of reproductive isolation between M. duodecimcostatus and M. lusitanicus through a laboratory crossbreeding experiment and two-way mate preference tests on the basis of chemical cues. Crossbreeding of sympatric individuals from the two species was successful and followed Haldane's rule, revealing hybrid male sterility and reduced fertility of hybrid females. Results from mate preference tests showed males of both pine vole species could discriminate and preferred female conspecifics to heterospecifics or hybrid females on the basis of chemical cues alone. On the contrary, females of both pine vole species did not show a clear preference for conspecific over heterospecific male chemical cues, suggesting females may need additional cues to discriminate between males of the two species. As a whole our results indicate both prezygotic (i.e. species-specific mate recognition systems) and postzygotic barriers (i.e. male hybrid sterility, female reduced fertility and behavioural sterility ― decreased ability to find or attract mates) have evolved, and should make hybridisation of the Iberian pine voles under natural conditions an unlikely event. The role of both species mating preferences and interspecific behavioural interactions in the asymmetric mitochondrial introgression pattern of the Iberian pine voles is discussed.